High occurrence of Blastocystis sp. subtypes 1–3 and Giardia intestinalis assemblage B among patients in Zanzibar, Tanzania. Issue 1 (December 2016) - Forsell, Joakim; Granlund, Margareta; Samuelsson, Linn; Koskiniemi, Satu; Edebro, Helén; Evengård, Birgitta
Abstract Background Blastocystis is a common intestinal parasite with worldwide distribution but the distribution ofBlastocystis and its subtypes in East Africa is largely unknown. In this study, we investigate the distribution ofBlastocystis subtypes in Zanzibar, Tanzania and report the prevalence of intestinal parasites using both molecular methods and microscopy. Methods Stool samples were collected from both diarrhoeic and non-diarrhoeic outpatients in Zanzibar. In addition to microscopy, real-time PCR forBlastocystis, Entamoeba histolytica andE. dispar, Giardia intestinalis, Cryptosporidium spp., andDientamoeba fragilis was used.Blastocystis subtypes were determined by a conventional PCR followed by partial sequencing of the SSU-rRNA gene. Genetic assemblages ofGiardia were determined by PCR with assemblage specific primers. Results Intestinal parasites were detected in 85 % of the 174 participants, with two or more parasites present in 56 %.Blastocystis sp. andGiardia intestinalis were the most common parasites, identified by PCR in 61 and 53 % of the stool samples respectively, but no correlation between carriage ofBlastocystis andGiardia was found. TheBlastocystis subtype distribution was ST1 34.0 %, ST2 26.4 %, ST3 25.5 %, ST7 0.9 %, and 13.2 % were positive only by qPCR (non-typable). TheGiardia genetic assemblages identified were A 6.5 %, B 85 %, A + B 4.3 %, and non-typable 4.3 %. The detection rate with microscopy was substantially lower than with PCR, 20 % forBlastocystis and 13.8 % forGiardia. The prevalence ofBlastocystis increased significantly with age whileGiardia was most prevalent in children two to five years old. No correlation between diarrhoea and the identification ofGiardia, Blastocystis, or their respective genetic subtypes could be shown and, as a possible indication of parasite load, the mean cycle threshold values in the qPCR forGiardia were equal in diarrhoeic and non-diarrhoeic patients. Conclusions Carriage of intestinal parasites was very common in the studied population in Zanzibar. The most commonly detected parasites, Blastocystis andGiardia, had different age distributions, possibly indicating differences in transmission routes, immunity, and/or other host factors for these two species. In theBlastocystis subtype analysis ST1-3 were common, but ST4, a subtype quite common in Europe, was completely absent, corroborating the geographical differences in subtype distributions previously reported.